Bioelectrical activity of the human brain - Mohd. Daud, Salwani; Yunus, Jasmy (Universiti Teknologi Malaysia, 2003)
The bioelectrical activity recorded from the human scalp is known as electroencephalogram (EEG). EEG consists of few types of waves in different frequency bands ranging from 0.5 Hz to 100 Hz with very low amplitude in microvolts. EEG is a signal with a good temporal resolution within millisecond range but a very poor spatial resolution. This article reviews some approaches to improve the spatial resolution such as spline surface Laplacian, cortical imaging and spatial deconvolution. In the first part, background of the subject and some EEG related researches will be presented